Ocular hypotensive effects of a Rho-associated protein kinase inhibitor in rabbits - Kamaruddin MI (Dove Medical Press, 2017)
Muhammad Irfan Kamaruddin,1,2 Momoko Nakamura-Shibasaki,1 Yu Mizuno,1 Yoshiaki Kiuchi1 1Department of Ophthalmology and Visual Sciences, Graduate School of Biomedical Sciences, Hiroshima University, Hiroshima, Japan; 2Department of Ophthalmology, Hasanuddin University, Makassar, South Sulawesi, Indonesia Purpose: Ripasudil is a novel Rho-associated protein kinase inhibitor that is used to treat ocular hypertension. However, the comparison of the intraocular pressure (IOP)-lowering effects between ripasudil alone and other ocular hypotensive drugs has not been studied thoroughly. The purpose of this study is to examine the ocular hypotensive effects of 0.4% ripasudil, 2% pilocarpine, 0.5% timolol and 0.1% dorzolamide in rabbits. We also studied the IOP changes when 0.4% ripasudil was combined with 2% pilocarpine, 0.5% timolol or 0.1% dorzolamide. Methods: One drop of saline solution, 0.4% ripasudil, 0.5% timolol, 2% pilocarpine or 1% dorzolamide or a combination of these agents was applied topically to the left eyes of eight healthy albino rabbits. Posttreatment changes in the IOP of albino rabbits were monitored using a rebound tonometer over a 5-h time course. Changes in IOP after application of saline served as the control. One-way analysis of variance and Dunnett’s post hoc tests were used for statistical analyses. Results: After topical instillation, 0.4% ripasudil resulted in significant decreases in IOP at 0.5 and 1 h compared with the control group. Treatment with timolol, pilocarpine or dorzolamide had no significant effect on IOP. Treatment with timolol, pilocarpine or dorzolamide in combination with ripasudil resulted in significant reductions in IOP at 1 h. However, none of these agents enhanced the IOP-lowering effects of ripasudil. Conclusion: Ripasudil has stronger IOP-lowering effects than timolol, pilocarpine or dorzolamide hypotensive agents in our rabbit model. Addition of timolol, pilocarpine or dorzolamide did not enhance the IOP-lowering effects of ripasudil alone. Keywords: ripasudil, timolol, pilocarpine, dorzolamide, intraocular pressure, rabbit